2018
DOI: 10.1101/318311
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Parkinson’s disease and dopamine on digit span measures of working memory

Abstract: Hospital, Bristol, UK, BS10 5NB. +44 (0)1174148186. John.grogan@bristol.ac.uk. 10 11 ACKNOWLEDGEMENTS 12 The authors thank BRACE for the use of their building, all the patients and 13 participants who took part in this research, and the funders (Wellcome [097081/Z/11/Z] and 14 Bristol Research into Alzheimer's and Care of the Elderly charity [BRI17/15]). 15 16 ABSTRACT 17 Rationale 18Parkinson's disease (PD) impairs working memory (WM) -the ability to maintain 19 items in memory for short periods of time and m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…This might be due to the older cohort with neurodegenerative disease, so that ‐ unlike in the healthy participants ‐ there was no further reserve to compensate the cognitive load of the concurrent task. In line with this hypothesis, previous studies have demonstrated that PD patients show impaired working memory capacity in the forward digit span task [41], which was used in the cognitive dual‐task paradigm. Also, PD patients might have to devote more cognitive attention to swallowing than healthy individuals.…”
Section: Discussionmentioning
confidence: 80%
“…This might be due to the older cohort with neurodegenerative disease, so that ‐ unlike in the healthy participants ‐ there was no further reserve to compensate the cognitive load of the concurrent task. In line with this hypothesis, previous studies have demonstrated that PD patients show impaired working memory capacity in the forward digit span task [41], which was used in the cognitive dual‐task paradigm. Also, PD patients might have to devote more cognitive attention to swallowing than healthy individuals.…”
Section: Discussionmentioning
confidence: 80%